Strategi Kepemimpinan Lembaga Pelatihan Kerja Hideo Gakkou Indonesia Kabupaten Batang - Kasda, Abdul; Murniati, Ngurah Ayu Nyoman; Wuryandini, Endang (PGRI Kota Semarang, 2024)
Abstract Problem formulation 1) what is the promotional strategy for LPK Hideo Gakkou Indonesia, Batang Regency; 2) what is the competency strategy for LPK Hideo Gakkou Indonesia students, Batang Regency; 3) how is the distribution and placement of work at LPK Hideo Gakkou Indonesia, Batang Regency. This research uses a qualitative approach, taking place at the Hideo Gakkou Indonesia Job Training Institute, Batang Regency. Data collection techniques are observation, interviews and documentation. The validity test uses source triangulation, technique triangulation and time triangulation. Data analysis uses include data collection, data reduction, data presentation and conclusion drawing. The results of the research include (1) LPK Hideo Gakkou Indonesia's promotional strategy (a) marketing mix (marketing product quality, low but quality prices, easily accessible places and clean AC facilities, promotion of innovative programs) (b) Promotional mix (Advertising), (c) Word of mouth communication (2) LPK Hideo Gakkou Indonesia student competency strategies include strengthening education and training, language learning ability tests, learning competencies, active learning citizens, Strengthening Japanese Language Training Skills, Tokutei Ginou Work Program (3) Distribution and Work placement at LPK Hideo Gakkou Indonesia includes the departure process, training and apprenticeship. Conclusion: The leadership strategy of the Indonesian Hideo Gakkou Job Training Institute in Batang Regency includes organizing promotional strategies, student competency strategies, distribution and job placement at LPK Hideo Gakkou Indonesia. Suggestions for the Hideo Gakkou Indonesia Job Training Institute (LPK), which currently still needs to be improved, are that they hope to form a special team in the marketing sector so that the marketing strategy can be better planned and conceptualized to build an image and gain public trust. Implications: Leadership strategies are a tool to realize success and create a better future for training institutions. With strategy, training institution leaders can realize their vision and mission in an effort to advance the institution and overcome various gaps within the institution. The role of institutional leaders is very important to increase driving factors and minimize inhibiting factors. Keywords: Leadership Strategy, Job Training Institute.